2007
DOI: 10.1148/radiol.2423052101
|View full text |Cite
|
Sign up to set email alerts
|

Lower Extremity Deep Venous Thrombosis: Evaluation with Ferumoxytol-enhanced MR Imaging and Dual-Contrast Mechanism—Preliminary Experience

Abstract: Institutional review board approval and informed consent were obtained for this HIPAA-compliant study, whose purpose was to prospectively evaluate the use of a dual-contrast mechanism in conjunction with an iron oxide blood pool contrast agent, ferumoxytol, to depict deep venous thrombosis (DVT). Nine patients with lower extremity DVT detected with duplex ultrasonography (US) were imaged with magnetic resonance (MR) imaging and ferumoxytol. Three techniques, including precontrast two-dimensional time-of-flight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 15 publications
1
44
0
2
Order By: Relevance
“…With contrast enhanced MRV unpredictable arrival of gadolinium based contrast in the more distal veins confounded by the very short transit time due to rapid redistribution into the extracellular fluid space led to development of "blood pool" contrast agent for calf veins imaging (65,66).…”
Section: Mr Imaging Of Vtementioning
confidence: 99%
See 2 more Smart Citations
“…With contrast enhanced MRV unpredictable arrival of gadolinium based contrast in the more distal veins confounded by the very short transit time due to rapid redistribution into the extracellular fluid space led to development of "blood pool" contrast agent for calf veins imaging (65,66).…”
Section: Mr Imaging Of Vtementioning
confidence: 99%
“…Li et al (66) prospectively evaluated the use of a dualcontrast mechanism in conjunction with an iron oxide blood pool contrast agent, ferumoxytol, to depict DVT. Three techniques, including precontrast 2D TOF, ferumoxytolenhanced bright-blood imaging, and ferumoxytol-enhanced dark-blood imaging, were applied focusing on its T1 as well as T2 relaxivity.…”
Section: Mr Imaging Of Vtementioning
confidence: 99%
See 1 more Smart Citation
“…Ferumoxytol may therefore be an attractive option for patients with renal function impairment since iron-based agents are not associated with risk of nephrogenic systemic fibrosis, and can be considered in vascular imaging when gadolinium-based agents are contraindicated. In addition, Li et al evaluated extremity deep venous thrombosis with Ferumoxytol-enhanced MR and found that image quality scores for Ferumoxytolenhanced MR were uniformly superior to those of noncontrast 2D time-of-flight images (average image quality score for Ferumoxytol was 3.6 vs. 1.4 for precontrast images) (1). Also, MR showed agreement with duplex US in depicting 90% of the thrombi and an increased detection of additional contralateral thrombi.…”
Section: Deep Venous Thrombosismentioning
confidence: 99%
“…Historically, one of the earliest imaging modalities used in venous imaging was ascending contrast venography, which is rarely used today due its invasiveness and risk of complications. Instead, ultrasound (US) has now become the modality of choice in clinical practice for the evaluation of deep vein thrombosis (DVT), with advantages in cost effectiveness, noninvasiveness, and portability in critically ill patients (1). However, key limitations of US exist, and include decreased sensitivity due to body habitus or edema, individual operator dependence (2), and difficulty in evaluation of calf veins and recurrent or chronic DVT (3).…”
Section: Introductionmentioning
confidence: 99%